Phrases marquantes in Annie Ernaux : From the Hyperconsciousness of the Language to a linguistic transfugivité in La Honte - Peñalver Vicea, Maribel (Verbum, 2025)
Some words can hurt, and they can hurt their receiver forever. From childhood, Annie Ernaux has been marked by the hard-hitting words that have had a bitter impact on her life. Yet writing has enabled her to overcome the burden of these words, the corollary being a language permeated by linguistic hypersensitivity, that is, a highly developed sensitivity to the use of language in literary texts. This article focuses on the role of linguistic hyperconsciousness in Annie Ernaux’s La Honte (1997) as a reflection of those hurting words that have been stored up and internalized in the author’s mind. From a theoretical viewpoint, this study draws mainly on the strengths of discourse analysis, as described in J. Authier-Revuz (2019, 2005), as well as on psychoanalysis, the notion of phrase marquante being originally introduced by psychoanalyst J.-A. Miller. In the literary field, the study builds upon L. Gauvin’s work on the notion of surconscience linguistique.